2023
DOI: 10.1021/acsanm.3c02186
|View full text |Cite
|
Sign up to set email alerts
|

A Nano-Delivery System Enhances the Stomach Toxicity of Methoxyfenozide against Spodoptera litura by Suppressing the Synthesis of Insect Cuticle Protein

Abstract: There is a growing demand for applying green pesticides instead of traditional synthetic pesticides to minimize potential threats to food and environmental safety. Insect growth regulators (IGRs) are regarded as a secure alternative, but their control efficacy needs to be improved to meet actual demands. Herein, a star polymer (SPc) was constructed and applied as an efficient pesticide nanocarrier, which could be spontaneously conjugated with IGR methoxyfenozide via hydrogen bonding with a high pesticide loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…SPc can self-assemble with various insecticides, such as imidaclothiz, methoxyfenozide, and thiamethoxam, to enhance their bioactivity. 23,24,37 In the current study, it was found that SPc could assemble with TTP into TTP/SPc complex via hydrogen bonding and van der Waals force, and the PLC was calculated to be 32.2%, which was relatively higher than those toward thiamethoxam (20.63%), cyantraniliprole (24.79%), and monosultap (19.3%). 23,58–60 The SPc can combine with an insecticide via various interactions, such as electrostatic interaction, hydrophobic interaction, and hydrogen bonding.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…SPc can self-assemble with various insecticides, such as imidaclothiz, methoxyfenozide, and thiamethoxam, to enhance their bioactivity. 23,24,37 In the current study, it was found that SPc could assemble with TTP into TTP/SPc complex via hydrogen bonding and van der Waals force, and the PLC was calculated to be 32.2%, which was relatively higher than those toward thiamethoxam (20.63%), cyantraniliprole (24.79%), and monosultap (19.3%). 23,58–60 The SPc can combine with an insecticide via various interactions, such as electrostatic interaction, hydrophobic interaction, and hydrogen bonding.…”
Section: Discussionmentioning
confidence: 66%
“…All other reagents were bought from Beijing Chemical Works (China). The SPc was synthesized in a two-step process following the methods described by Li et al 22 and Jiang et al 37 In the initial step, a solution containing pentaerythritol in dry THF and triethylamine at 0 °C was subjected to the gradual addition of 2-bromo-2-methylpropionyl bromide. After stirring for 24 h, the reaction was terminated with methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table , the PLC of SPc toward spirotetramat was examined using the freeze-drying method, and it was calculated to be 36.16%, which was comparable to methoxyfenozide (32.66%) and higher than dinotefuran (17.41%) and thiamethoxam (20.63%). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Our group has designed and synthesized a star polymer (SPc) as an efficient nanocarrier for various substances . The SPc-based nanodelivery system is fit for the efficient delivery of nucleic acids and synthetic/botanical pesticides. The SPc can assemble with several synthetic/botanical pesticides spontaneously, including osthole, matrine, dinotefuran, thiocyclam, methoxyfenozide, etc. , The self-assembly with SPc can reduce the particle sizes of pesticides and improve their delivery efficiency for enhanced bioactivity. We have confirmed that the bioactivities of SPc-loaded pesticides can be improved by 20–40% compared with conventional pesticides.…”
Section: Introductionmentioning
confidence: 99%